DETERMINATION OF THE CAUSES AND CHARACTERISTICS OF SINGLE-PHASE GROUND CIRCUITS IN DISTRIBUTION NETWORKS WITH A VOLTAGE OF 6-35 KV - KUTIN, Vasyl; KUTINA, Maryna; KOVALYOV, Artem; ROMANIUK, Mykola (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Abstract. The analysis of statistical data showed that the most common type of damage to distribution networks is single-phase earth faults, which account for 80% of all types of damage. The main cause of earth faults is the formation of shunt connections between the current-conducting part and the earth. The reason for their occurrence is external factors: lightning overlapping insulation, overlapping insulation with tree branches, ice, wind load, vibration of networks, burning of wooden supports, damage to supports by various mechanisms. Cable networks are damaged due to a violation of their mechanical stability and due to the aging of the insulation between the phases and the belt insulation. In the work, the classification of single-phase earth faults is performed. In general, the whole variety of single-phase earth faults can be divided into two groups - non-arcing and arcing. An accurate mathematical description of the processes of single-phase earth faults accompanied by an electric arc is a significant difficulty due to the fact that the electrical resistance of a steadily burning arc is a non-linear function of the current flowing through it. A. M. Lyapunov's stability theory was used to find out the conditions of arc stability during a single-phase earth fault. The grid replacement scheme for single-phase arcing to the ground is constructed. It was determined that the arc is formed under the action of two currents: from the discharge of the capacity of the small circuit (free current) and from the EMF source of the large circuit (forced current). Since the nature of the transition process is mainly determined by the free component, its analysis was carried out. It was determined that it is extremely important for practical purposes to acquire quantitative values not only of resistance, but also of the duration of existence of self-eliminating circuits.The parameters of the single-phase ground fault circuit in the electrical network, motors, transformers, the stability conditions of single-phase ground faults have been investigated.
Keywords: distribution network; insulation damage; electric arc